Zeolite Encapsulated Nanocrystalline CuO: A Redox Catalyst for the Oxidation of Secondary Alcohols. (13th May 2008) - Vijaikumar, Sakthivel; Subramanian, Thirumeni; Pitchumani, Kasi
Abstract : Zeolite encapsulated nanocrystalline CuO is synthesized and characterized by powder XRD and HRTEM analyses which clearly show that the particles are less than 15 nm and the nanoparticles are highly dispersed. This nano CuO encapsulated CuY zeolite is used as catalyst in the oxidation of aromatic secondary alcohols. CuY zeolite acts as an efficient support for nano CuO, by stabilizing it and preventing its aggregation. Plausible mechanisms for the formation of the various products are also given.